Rotational alignment of the tibial component in total knee arthroplasty is better at the medial third of tibial tuberosity than at the medial border - Lützner, Jörg (BioMed Central, 2010)
BACKGROUND: Correct rotational alignment of the femoral and tibial component is an important factor for successful TKA. The transepicondylar axis is widely accepted as a reference for the femoral component. There is not a standard reference for the tibial component. CT scans were used in this study to measure which of 2 tibial landmarks most reliably reproduces a correct femoro-tibial rotational alignment in TKA. METHODS: 80 patients received a cemented, unconstrained, cruciate-retaining TKA with a rotating platform. CT scans were performed 5-7 days postoperatively but before discharge. The rotational mismatch between the femoral and tibial components was measured. Furthermore, the rotational variance between the transepicondylar line, as a reference for the orientation of the femoral component and different tibial landmarks, was measured. RESULTS: There was notable rotational mismatch between the femoral and tibial components. The median mismatch was 0° (range: 16.2 degrees relative external to 14.4 degrees relative internal rotation of the femoral component). Using the transepicondylar line as a reference for femoral rotational alignment and the medial third of the tuberosity as a reference for tibial rotational alignment, 67.5% of all TKA had a femoro-tibial variance within ± 5 degrees, 85% within ± 10 degrees and 97.5% within ± 20 degrees. Using the medial border of the tibial tubercle as a reference this variance was greater, only 3.8% had a femoro-tibial variance within ± 5 degrees, 15% within ± 10 degrees and 68.8% within ± 20 degrees. CONCLUSION: Using fixed bone landmarks for rotational alignment leads to a notable variance between femoral and tibial components. Referencing the tibial rotation on a line from the medial third of the tibial tubercle to the center of the tibial tray resulted in a better femoro-tibial rotational alignment than using the medial border of tibial tubercle as a landmark. Surgeons using fixed bearings with a high rotational constraint between the inlay and the femoral component should be aware of this effect to avoid premature polyethylene wear. TRIAL REGISTRATION: Clinical trials registry NCT01022099